1984
DOI: 10.1073/pnas.81.18.5782
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mRNAs for alpha- and beta-tubulin during differentiation of the parasitic protozoan Leishmania mexicana.

Abstract: The parasitic protozoan Leishmania mexicana amazonensis has two developmental stages: a motile flagellated promastigote stage and a sessile intracellular amastigote stage. In our previous work, cells of the promastigote stage were found to synthesize more tubulin protein than those of the amastigote stage. Here, tubulin mRNAs in these leishmanias were analyzed. Based on dot blot hybridization between total leishmanial RNA and tubulin-specific cDNA probes derived from chicken brain, amastigotes and promastigote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
2

Year Published

1986
1986
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 36 publications
4
16
0
2
Order By: Relevance
“…4H) increased in abundance in intracellular amastigotes but not in axenic amastigotes. A similar pattern of differentially regulated ␤-tubulin transcript sizes has been reported for Leishmania amazonensis (30). In summary, three constitutively expressed RNAs (␣-tubulin, LmGT1, LmGT3), three RNAs that are down-regulated in amastigotes (LmGT2, PFR-1, ␤-tubulin 2.4-kb transcript), and two RNAs that are up-regulated in amastigotes (cysteine protease-2 and ␤-tubulin 2.8-kb transcript) are correctly regulated in axenic amastigotes.…”
Section: Regulation Of Lmgt Gene Expression In Promastigotes Andsupporting
confidence: 77%
“…4H) increased in abundance in intracellular amastigotes but not in axenic amastigotes. A similar pattern of differentially regulated ␤-tubulin transcript sizes has been reported for Leishmania amazonensis (30). In summary, three constitutively expressed RNAs (␣-tubulin, LmGT1, LmGT3), three RNAs that are down-regulated in amastigotes (LmGT2, PFR-1, ␤-tubulin 2.4-kb transcript), and two RNAs that are up-regulated in amastigotes (cysteine protease-2 and ␤-tubulin 2.8-kb transcript) are correctly regulated in axenic amastigotes.…”
Section: Regulation Of Lmgt Gene Expression In Promastigotes Andsupporting
confidence: 77%
“…As expected, the tubulin amino acid sequences from L. tarentolae are highly similar to the tubulin sequences from other Leishmania species and with other organisms. Leishmania species possess a single mRNA for α-tubulin (Fong et al, 1984;Burchmore and Landfear, 1998), while multiple β-tubulin mRNAs have been observed in this parasite. Three distinct β-tubulin mRNAs have been detected in L. amazonensis (Fong et al, 1984) and L. major (Coulson et al, 1996), while multiple β-tubulin mRNAs were also found in L. mexicana (Burchmore and Landfear, 1998).…”
Section: Sequences Of L Tarentolae α-And β-Tubulin Genes and Comparimentioning
confidence: 98%
“…Leishmania species possess a single mRNA for α-tubulin (Fong et al, 1984;Burchmore and Landfear, 1998), while multiple β-tubulin mRNAs have been observed in this parasite. Three distinct β-tubulin mRNAs have been detected in L. amazonensis (Fong et al, 1984) and L. major (Coulson et al, 1996), while multiple β-tubulin mRNAs were also found in L. mexicana (Burchmore and Landfear, 1998). The identity between amino acid sequences for L. tarentolae agr;-tubulin and α-tubulins from L. donovani, L. major and L. infantum present in available databases is 98% or greater, while the identity between the L. tarentolae β-tubulin sequence reported here and the various β-tubulin sequences (from L. infantum, L. brazilensis, L. major, L. mexicana, and L. amazonensis) is at least 96%.…”
Section: Sequences Of L Tarentolae α-And β-Tubulin Genes and Comparimentioning
confidence: 98%
“…Restriction enzyme digests of human placental DNA (a generous gift from Peter W. Melera, Sloan-Kettering Institute) were subjected to electrophoresis through 0.8% agarose gel and transferred to nitrocellulose filters by the method of Southern (26), and hybridized with nick-translated Pst/Eco insert fragment from the clone pCB-1 (27 room temperature (2x NaCl/Cit with 0.5% NaDodSO4) and 680C (0.lx NaCl/Cit with 0.5% NaDodSO4).…”
mentioning
confidence: 99%